Effects of marine actinomycete on the removal of a toxicity alga Phaeocystis globose in eutrophication waters - Zhang, Huajun; Zhang, Su; Peng, Yun; Li, Yi; Chen, Zhangran; Xu, Hong; Yu, Zhiming; Zheng, Wei; Zheng, Tianling (Frontiers in Microbiology, 2015)
Phaeocystis globosa blooms in eutrophication waters can cause severely damage in marine ecosystem and consequently influence human activities. This study investigated the effect and role of an algicidal actinomycete (Streptomyces sp. JS01) on the elimination process of P. globosa. JS01 supernatant could alter algal cell membrane permeability in 4 h when analyzed with flow cytometry. Reactive oxygen species (ROS) levels were 7.2 times higher than that at 0 h following exposure to JS01 supernatant for 8 h, which indicated that algal cells suffered from oxidative damage. The Fv/Fm value which could reflect photosystem II (PS II) electron flow status also decreased. Real-time PCR showed that the expression of the photosynthesis related genes psbA and rbcS were suppressed by JS01 supernatant, which might induce damage to PS II. Our results demonstrated that JS01 supernatant can change algal membrane permeability in a short time and then affect photosynthesis process, which might block the PS II electron transport chain to produce excessive ROS. This experiment demonstrated that Streptomyces sp. JS01 could eliminate harmful algae in marine waters efficiently and may be function as a harmful algal bloom controller material.